2019
DOI: 10.21203/rs.2.18488/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Preliminary results of a screening programme for Chlamydia in an asymptomatic young population

Abstract: Introduction Chlamydia trachomatis infection has increased in recent years, reaching 127 million cases in 2016. Possible complications, especially among women, require intervention for early detection. The objective of our study was to determine the prevalence of Chlamydia infection in a young, sexually active, asymptomatic population.Methods A cross-sectional study was conducted among young patients aged 18 to 25 years attending the emergency room for any reason. The presence of Chlamydia trachomatis and othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Our team is developing a screening program 11 in the asymptomatic population of men and women between 18 and 25 years of age (preliminary data pending pub-lication), and we found that the prevalence of CT infection was as high as 7.4% among this asymptomatic sample of young patients attending our emergency department due to other health problems. However, although recommended by the ECDC, screening in sexually active young patients between the ages of 15 and 25 years is not being carried out in our country.…”
Section: Methods and Resultsmentioning
confidence: 94%
“…Our team is developing a screening program 11 in the asymptomatic population of men and women between 18 and 25 years of age (preliminary data pending pub-lication), and we found that the prevalence of CT infection was as high as 7.4% among this asymptomatic sample of young patients attending our emergency department due to other health problems. However, although recommended by the ECDC, screening in sexually active young patients between the ages of 15 and 25 years is not being carried out in our country.…”
Section: Methods and Resultsmentioning
confidence: 94%
“…Violant Pujol, Ms. Noemí Espies, Ms. Núria Garcia, and Mr. Àlvar Sole their contribution in the data collection. This manuscript has been released as a pre-print at research square ( 42 ).…”
mentioning
confidence: 99%